Agricultural research policy in an era of privatization [ - Byerlee, Derek; Echeverria, Ruben G. (CABI, 2002)
This book synthesizes contemporary experiences with changing public and private sector roles in funding and executing agricultural research, with emphasis on developing countries. The book consists of 15 chapters organized into four distinct parts. PartI provides a brief overview of the current status, trends and policy issues in public and private agricultural research and development in developing countries. The remaining parts of the book consist of case studies of recent experiences in exploring alternative mechanisms for funding and organizing agricultural research in an environment of privatization. Part II assesses public-private collaboration in financing research through commodity levies paid by farmers, and part III evaluates public-private collaboration in provision of research services through joint ventures and other types of partnerships. Part IV focuses on responses of public research organizations to privatization.